Adherence to Mediterranean diet in Moroccan school-age adolescents: sociodemographic, socioeconomic and lifestyle determinants - Halima Belaoufi; Sanaa El-Jamal; Khadija Sahel; Abdelghani Aboukhalaf; Firdaous Friki; Hamid Chamlal; Jamila Elbiyad; Soumaya Atouife; Abdellah El Habazi; Rekia Belahsen (Roczniki Panstwowego Zakladu Higieny)
Background Despite its benefits, the Mediterranean diet (MD) is abandoned or not adopted by the younger generations in most Mediterranean countries.